Seroprevalence of MOG and AQP4 Antibodies and Outcomes in an Indian Cohort of Pediatric Acquired Demyelinating Syndromes - Sankhyan, Naveen; Rawat, Amit; Vyas, Sameer; Sahu, Jitendra Kumar; Bhagwat, Chandana; Madaan, Priyanka; Saini, Lokesh; Saini, Arushi Gahlot; Suthar, Renu; Sukhija, Jaspreet; Jayashree, Murlidharan (Neuropediatrics, 2022)
This study aimed to determine the seropositivity of myelin oligodendrocyte glycoprotein antibodies (MOG-Ab) and aquaporin-4 antibodies (AQP4-Ab) and outcomes in children with acquired demyelinating syndromes (ADSs). Children (6 months–15 years) with suspected ADS were enrolled and tested for MOG-Ab and AQP4-Ab prospectively over 18 months at a tertiary care hospital in North India. Children with proven nonimmune-mediated neurological disorders were enrolled as controls. Of 79 children with suspected ADS, 66 were enrolled. Among the enrolled children with ADS, acute demyelinating encephalomyelitis (ADEM) (25) was the most common first clinical event followed by optic neuritis (ON) (20) and transverse myelitis (TM) (19; one child had ON and TM simultaneously [neuromyelitis optica spectrum disorders [NMOSDs]]), while two children had clinically isolated syndrome (CIS) apart from ON and TM. Fourteen (21.2%, confidence interval [CI] 11.3–31.1) tested positive for one antibody (12 [18.1%; 95% CI 10.5–25.5%] for MOG-Ab and 2 [3%; 95% CI 0–7.2%] for AQP4-Ab). None of the 62 controls tested positive for any antibody. The final diagnosis in those with the monophasic ADS was ADEM (21), ON (13), TM (16), and other CIS (1) while that in children with recurrent events was multiphasic disseminated encephalomyelitis (MDEM) (2), NMOSD (3), ADEM-ON (4), recurrent ON (4), and MS (2). Among those with the first event, 4/51 (7.8%; 95% CI 0.5–15.2%) were MOG-Ab positive and 2 AQP4-Ab positive, whereas 8/15 (53.3% [95% CI 28.1–78.6%]) with recurrent events (MDEM [2], ADEM-ON [4], recurrent ON [1], and recurrent TM [1]) were MOG-Ab positive. Hence, MOG-Abs are the most common antibodies detected in one in five children with pediatric ADS, especially in relapsing disease. AQP4-Abs are rare in children with ADS.
Keywords: demyelination; children; MOG; AQP-4